Role of central lymphadenectomy in managment of differentiated thyriod cancer - Mohammed Mamdoh Ahmed Asar; Mohamed Kamel El Awady; Ahmed Seddik Abdelgelil; Mohammed El Sharkawy; Osama Mostfa Mostafa (Wolters Kluwer Medknow Publications, 2019)
Background Differentiated thyroid cancers may be associated with regional lymph node (LN) metastases in 20-50% of cases. Papillary thyroid cancer is the most common thyroid malignancy, and cervical nodal metastases are frequent at presentation. Objective This study aims to detect the therapeutic and prophylactic results of centeral neck dissection (CND) in an adjunct to total thyroidectomy for the treatment of differentiated thyroid cancer and its effect in reducing local recurrences and the need for postoperative radioiodine ablation. Patients and methods This study was carried out on 30 patients with thyroid cancers. They were managed at Oncological Surgery Departments of Al-Azhar University between January 2017 and August 2018. This study included 30 patients, comprising 10 (33.3%) males and 20 (66.6%) females, and their ages ranged from 26-82 years old, with a mean age of 51 years. They all underwent total thyroidectomy and CND for differentiated thyroid cancer, which was proved preoperatively by fine-needle aspiration from thyroid swelling. Neck ultrasound and high-resolution neck computed tomographic scan with contrast were done to detect size and extension of thyroid cancer and any concerning LNs. Results The analysis of nodal spreading in this study showed an ipsilateral central nodal metastasis on the same side of affected lobe and bilateral central LN metastasis when the tumor arose within each lobe or from isthmus, as the lesions from isthmus had wide diffusion. Moreover, this study showed tumors with size of 20 less than or equal to T2 less than 40 mm associated with the presence of LN metastases were subjected to postoperative 131I ablation, and also a size greater than or equal to 40 mm with vascular invasion or tumor extension beyond the thyroid capsule even not associated with the presence of LN metastases were subjected to postoperative 131I ablation. Conclusion Prophylactic central compartment neck dissection (ipsilateral or bilateral) should be considered in patients with differentiated thyroid cancer (DTC) with clinically noninvolved central neck LNs (cN0) who have locally advanced primary tumors (T3 or T4), and prophylactic ipsilateral CND and lateral neck dissection for DTC less than 2 cm in diameter allowed selection of patients for postoperative 131I ablation and modified the indication for 131I ablation in patients with pT1 tumors.